Gatewaying IEEE 1149.1 and IEEE 1149.7 test access ports - José Martins Ferreira (2012)
In this paper, we present a description of our developed adapter, which takes acts as a gateway between IEEE 1149.1 and IEEE 1149.7 test infrastructures. The referred adapter reduces the pins of the TAP from 4 to 2 and implements advanced capabilities, such as Parking State of a TAPC and the Reset and Selection Unit (RSU).